2014
DOI: 10.2147/ijn.s49976
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic particle imaging: kinetics of the intravascular signal in vivo

Abstract: Background Magnetic particle imaging (MPI) uses magnetic fields to visualize superparamagnetic iron oxide nanoparticles (SPIO). Today, Resovist ® is still the reference SPIO for MPI. The objective of this study was to evaluate the in vivo blood half-life of two different types of Resovist (one from Bayer Pharma AG, and one from I’rom Pharmaceutical Co Ltd) in MPI. Methods A Resovist concentration of 50 μmol/kg was injected into the ear artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…a blood pool tracer [21, 22]. That is because Resovist is cleared quickly from the blood stream by liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a blood pool tracer [21, 22]. That is because Resovist is cleared quickly from the blood stream by liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for larger particles and particle clusters, which contribute more to the MPI signal of Resovist than its smaller particles [23]. Data in mice using the very sensitive Magnetic Particle Spectroscopy (MPS) show that the signal of Resovist in blood drops below noise level after 15–30 minutes without even reaching a steady state first [22]. After 5 minutes, a maximum of 40% of the initial signal could be measured.…”
Section: Discussionmentioning
confidence: 99%
“…[24] As such, MPI offers high image contrast (with negligible background signal from diamagnetic tissue), a signal linear with tracer concentration [25] and zero depth attenuation, and is safe as it uses no ionizing radiation, as compared with many other biomedical imaging methods. Additionally, a demonstrated high sensitivity (200 nm Fe) [26] and high temporal resolution [27] is achieved when optimized SPIONs of tailored size and size dispersity are used [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, increasing PEG molecular weight from 5 kDa to 20 kDa led to a near doubling in t 1/2 ; on the other hand, preliminary results suggest that around 18.8% PEG loading provided the longest t 1/2 (160 minutes) when using a 20 kDa PEG. For comparison, independent pharmacokinetic studies with Resovist nanoparticles reported less than 5 minutes of blood half-life [1,2]. …”
Section: Resultsmentioning
confidence: 99%